Effects Of Gambir Extract Treatment On The Rusted Mild Steel - Dahon, Nur Hazwani (2013)
Uncaria gambir was extracted using six different solvents and the effects on the extraction yield and phenolic contents were investigated. The phenolic contents, namely, total phenolic (TPC), total flavonoid (TFC), condensed tannin (CTC) and antioxidant activity (AA) of the gambir extracts were quantified. Ethyl acetate solvent was found successfully extracted the highest TPC (93% catechin equivalent), TFC (91% catechin equivalent) and CTC (96% weight). Besides, the phenolic content shows the ability of gambir extract as antioxidant. The performance of gambir extract as rust converter was evaluated. The effects of gambir concentration, pH solution, contact time and the addition of phosphoric acid in rust converter were studied. The FTIR spectra showed that the conversion of lepidocrocite (γ-FeOOH) was the fastest, followed by magnetite (Fe3O4) and goethite (α-FeOOH) was the slowest. The effectiveness of rust conversion coatings was studied via EIS and potentiodynamic polarization. The Tafel and Nyquist plots analyses were in agreement showing that increasing the gambir concentration decreased the corrosion rate and the mixture of 10% gambir and 5% H3PO4 produced a better rust converter. The changes in morphology of the rust were significant as viewed by SEM analysis. The spike-shaped rust was converted into a more homogeneous and compact surface after treatment with rust converter. XRD patterns showed a decrease of the rust products after being treated with gambir-based rust converter.